1993
DOI: 10.3382/ps.0722200
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Crude and Refined Palm and Palm Kernel Oils in Broiler Diets

Abstract: Four experiments were conducted to evaluate the use of crude and refined palm (PAO) and palm kernel oil (PKO) in diets for broiler chickens. In Experiment 1, refined PAO and PKO were compared with corn oil (CO) and poultry oil (PO) at levels up to 10%. In Experiment 2, refined PAO and PKO were compared with PO at levels up to 8%. In Experiments 3 and 4, crude PAO and PKO were compared with PO at levels up to 8%. Diets were formulated based on the energy level assigned to PAO; other oils were added in amounts c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 21 publications
3
10
1
Order By: Relevance
“…This suggests that the two fat sources have similar digestibility. A similar response was obtained by Valencia et al (1993) who reported that there were no effects of the sources of oil (refined palm oil, palm oil, corn oil and poultry fat) on BWG and FCR in broilers. The result is congruent with previous findings of Abudabos (2013), who reported that birds that received KOF or SBO responded equally.…”
Section: Discussionsupporting
confidence: 63%
“…This suggests that the two fat sources have similar digestibility. A similar response was obtained by Valencia et al (1993) who reported that there were no effects of the sources of oil (refined palm oil, palm oil, corn oil and poultry fat) on BWG and FCR in broilers. The result is congruent with previous findings of Abudabos (2013), who reported that birds that received KOF or SBO responded equally.…”
Section: Discussionsupporting
confidence: 63%
“…The results with respect to the FA composition of the broiler meat samples indicate that meat from broiler chickens fed diets containing HKO, singly or combined with SO could be an important source of oleic acid for human diets, because the common FA in the diet was most abundant in the meat. This result supports the idea that in monogastric animals the FA composition of the tissues will reflect that of the diet 13, 18–21. The replacement of SO with HKO in broiler diets results in a significant increase of the oleic acid which is the most predominant MUFA in meat and, consequently, leads to a decrease in the SFA:MUFA ratio.…”
Section: Discussionsupporting
confidence: 84%
“…These changes in proportion of fatty acids resulted in the highest and lowest PUFA:SFA ratio in the SB and PK oil treatments, respectively, particularly in thigh muscle. In a similar study in broilers, Valencia et al (1993) also reported that PK oil induced deposition of lauric fatty acid (C12:0), increased the proportion of SFA, and reduced MUFA and PUFA in muscle, compared with palm or poultry oil used as a lipid source in the diet. A similar effect from PK oil was reported in pigs as well (Teye et al, 2006).…”
Section: Discussionmentioning
confidence: 90%